Phonological Errors in Pronouncing Basa Osing: Analysis of Language Behavior - Delijar, Ressi Maulidina (Universitas Ahmad Dahlan, 2019)
This research aims to determine the language behavior of Basa Osing speakers in phonological aspects. This research is important because of the debate over the Basa Osing linguistic status which considers that Basa Osing is only a variation of Javanese, and the other assumption that Basa Osing is an independent local language. This kind of situation will probably affect the behavior of Basa Osing speakers. This research used qualitative methods and collecting data by using silent movie and picture. The participants involved in this research are 10 Basa Osing speakers. Errors found in pronouncing Basa Osing are in form of ignoring the diphtongization of vocals /i/ and /u/ at the end of the word and the palatalization of /b/ at the beginning and at the middle of the word, /d/ at the middle of the word, /D/ at the middle of the word, /g/ at the beginning and middle of the word, and /m/ in the middle of the word, so that the spoken word sounds more like a word in Javanese than Basa Osing.This research aims to determine the language behavior of Basa Osing speakers in phonological aspects. This research is important because of the debate over the Basa Osing linguistic status which considers that Basa Osing is only a variation of Javanese, and the other assumption that Basa Osing is an independent local language. This kind of situation will probably affect the behavior of Basa Osing speakers. This research used qualitative methods and collecting data by using silent movie and picture. The participants involved in this research are 10 Basa Osing speakers. Errors found in pronouncing Basa Osing are in form of ignoring the diphtongization of vocals /i/ and /u/ at the end of the word and the palatalization of /b/ at the beginning and at the middle of the word, /d/ at the middle of the word, /D/ at the middle of the word, /g/ at the beginning and middle of the word, and /m/ in the middle of the word, so that the spoken word sounds more like a word in Javanese than Basa Osing.